THEORETICAL CONCEPTS OF INTERNATIONAL TRADE AND ECONOMIC RELATIONS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article looks at how ideas of international trade have changed over time. Theories appeared in different periods and reflected the challenges of their age. Some of them stressed the gains from exchange, others pointed to risks and limits. Turning to this legacy still matters today. It helps to see patterns in global economic development and gives ground for trade policy choices in the present.